-3=5x-4x-6

Simple and best practice solution for -3=5x-4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=5x-4x-6 equation:


Simplifying
-3 = 5x + -4x + -6

Reorder the terms:
-3 = -6 + 5x + -4x

Combine like terms: 5x + -4x = 1x
-3 = -6 + 1x

Solving
-3 = -6 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + -1x = -6 + 1x + -1x

Combine like terms: 1x + -1x = 0
-3 + -1x = -6 + 0
-3 + -1x = -6

Add '3' to each side of the equation.
-3 + 3 + -1x = -6 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -6 + 3
-1x = -6 + 3

Combine like terms: -6 + 3 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 12=6+2y | | 15/(3x4-(5-4)-6) | | -18x^3=-105x+150x | | (-8-2)3-(-4-6-2)= | | 0.50(4x+9)=18 | | 0-2y=48 | | X=(24-2y)/5=2 | | -j+2=-14 | | 2x-2+4x=5x+9 | | x*-3x=10 | | 2t(3t-4)+t(2t+5)= | | (5-2i)(-2+4i)= | | X*1/3=2x-4 | | -6(-4x+8)-2x=6(x-5)-8 | | 5x+5=-90 | | 47+628=17 | | 16-x-4y=0 | | -9n-8(2+2n)=-28 | | 35000+250p=17615+550p | | 5a^2+2b^2=10cforb | | 3-6x+6x+12=12x-24 | | (-4)+x=(-7) | | .83v+10=5 | | (-8-3)3-(4-6-2)= | | 17615+550p=74815 | | 3x-25=2x+2 | | -8x+4(x+2x-8)=-12 | | 0.4(x-3.5)=5.8x+1.84 | | 5/2a-5=30 | | 3x^8+30x^7+48x^6=0 | | (5-11i)-(-7+5i)= | | 75*60=95*40x |

Equations solver categories